Aporte ambiental de la planta de tratamiento de aguas residuales Los Tajos en la remoción de contaminantes fisicoquímicos y microbiológicos - Mora Aparicio, Carmen (2022)
The objective of the study was to analyze the environmental contribution, in terms of removal of physicochemical and microbiological pollutants, from the Los Tajos Wastewater Treatment Plant (WWTP) to the Torres River. Physicochemical and microbiological data was analyzed including WWTP inflows and outflows (OBD, OCD, TSS, STT, N-NH4 +, P-PO4 3-, Oils, MBAS, and fecal coliforms). The difference in the concentration of pollutants in the Torres River before and after the construction of the WWTP was analyzed using R 3.6.1, associated with seasonality. According to the Dutch Index Methodology, the Torres River was severely polluted before the construction of the WWTP, and the degree of contamination increases following the WWTP discharge, mainly during the rainy season. The WWTP shows significant removal of seven of the eight parameters analyzed, with the most representative removal percentages being: TSS (68.5%), OBD (49.8%), and Oils (54.7%). The quantitative contribution of the WWTP to the Torres River was demonstrated by removing thousands of Mg of pollutants from wastewater during the years of operation (2015-2020), mainly OCD (26,791.8 Mg), STT (24,162.6 Mg), OBD (12,290.0 Mg), and TSS (30,267.7 Mg). Finally, building the WWTP’s next stages, including secondary treatment, is needed to improve the removal of organic matter, surfactants, and nutrients.